Time, memory and the verbal arts: Essays on the thought of Walter Ong - Weeks, Dennis L.; Hoogestraat, Jane (Cranbury Associated university press, 1998)
The original essays in this book explore the implications of Ong's work across the diverse fields of cultural history, literary theory, theology, philosophy, and anthropology. These scholars argue that Ong's view of orality not only changes our readings of ancient and medieval texts but that it also changes our understanding of the differing epistemologies of the oral and literate within a given culture.